Efektivitas Program PKPR terhadap Kesehatan Reproduksi Remaja di Puskesmas Sigambal - Wijaya, Arini Aisyahfira; Agustina, Dewi; Utami, Tri Niswati (Jurnal Biomedika dan Kesehatan, 2025)
Background the Adolescent Care Health Service Program (PKPR) plays a crucial role in improving adolescent reproductive health. Adolescents experience various physical, psychological, and social changes that influence their knowledge and behavior regarding reproductive health. In Indonesia, adolescent reproductive health needs serious attention because 18.55% of adolescents marry at a young age (16-18 years), with 2.39% marrying before age 16. Additionally, 43.55% of young women give birth before age 21. However, the implementation of the PKPR program still faces multiple challenges that hinder its optimal impact. Methods This study used a descriptive qualitative approach, collecting data through direct observation and in-depth interviews with program implementers and adolescent beneficiaries in the working area of Sigambal Public Health Center. Results The PKPR program at Sigambal Health Center faces several obstacles, including low adolescent participation (17.52%), infrequent and ineffective counseling sessions, and limited outreach and socialization. Out-of-school adolescents are not reached effectively, and the role of peer counselors has not been strengthened. Moreover, adolescents' low awareness of the importance of reproductive health services limits the program’s effectiveness. Conclusions While the PKPR program has shown a positive impact on some adolescents, its overall effectiveness remains limited. Expanding coverage, increasing activity frequency, strengthening peer counselor involvement, and developing more innovative outreach strategies are essential to ensure broader and more sustainable adolescent engagement.